Evaluasi Traffic Profile Pada Jaringan Data Existing Universitas Riau - Abiyyah, Liandri Talitha; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Quality Of Service is very significant to measures data network performance indicator in the existing system in Riau University. This paper discusses performance analysis of existing datanetworks Riau University. The detail of performance analysis consists of several parameters such as throughput, packet loss and delay. It uses approach Action Research. The measurement was conducted when idle condition. The result shows Economics Faculty in good performance and the opposite result is indicated by Fisheries Faculty. Traffic problems arising from accessing the peak season occurs due to scheduling KRS which does not refer to the numberof each user on the faculties.Keywords : Quality Of Services, Delay, Throughput, Packet Loss